Aplikasi Kounseling Dalam Pelaksanaan Kurikulum Pendidikan Islam - Erlina, Nova (Universitas Islam Negeri Raden Intan Lampung, 2014)
Abstract: In general, counseling is a process to help a person get a mind-set (insegth) so that can make choices or make decisions about a problem or problem in the face. However, some aspects of counseling, as well as impressive features of kaunselor can also be applied in the teaching and learning process. As a method and technique has been used in teaching and learning process with the subject of teaching. Implementation of counseling in teaching and learning process is expected to improve the process of teaching and learning process. This paper discusses the kununing of the Islamic persipektif and application of Islamic kaunseling techniques that may be applied to the framework and implement the curriculum of Islamic education, ie from the aspects of teachers and lesson